Bioinformatics prediction and experimental validation of a novel microRNA: hsa‐miR‐B43 within human CDH4 gene with a potential metastasis‐related function in breast cancer. Issue 2 (6th September 2019) - Rahimi, Azadeh; Sedighi, Rina; Emadi‐Baygi, Modjtaba; Honardoost, Mohammad‐Amin; Mowla, Seyed‐Javad; Khanahmad, Hossein; Nikpour, Parvaneh
Abstract: As a class of short noncoding RNAs, microRNAs (miRNAs) play a key role in the modulation of gene expression. Although, the regulatory roles of currently identified miRNAs in various cancer types including breast cancer have been well documented, there are many as yet undiscovered miRNAs. The aim of the current study was to bioinformatically reanalyze a list of 189 potentially new miRNAs introduced in a previously published paper (PMID: 21346806) and experimentally explore the existence and function of a candidate one: hsa‐miR‐B43 in breast cancer cells. The sequences of 189 potential miRNAs were re‐checked in the miRbase database. Genomic location and conservation of them were assessed with the University of California Santa Cruz (UCSC) genome browser. SSC profiler, RNAfold, miRNAFold, MiPred, and FOMmiR bioinformatics tools were furthermore utilized to explore potential hairpin structures and differentiate real miRNA precursors from pseudo ones. hsa‐miR‐B43 was finally selected as one of the best candidates for laboratory verification. The expression and function of hsa‐miR‐B43 were examined by real‐time polymerase chain reaction, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide, and wound‐healing assays. DIANA‐microT, RNAhybrid and Enrichr tools were used to predict the miRNA target genes and for further enrichment analysis. We could detect the exogenous and endogenous expression of hsa‐miR‐B43, as a real novel miRNA, in cancer cell lines. Gene Ontology enrichment, pathway analysis and wound‐healing assay results furthermore confirmed that a metastasis‐related function may be assigned to hsa‐miR‐B43. Our results introduced hsa‐miR‐B43, as a novel functional miRNA, which might play a role in the metastatic process. Further studies will be necessary to completely survey the existence and function of hsa‐miR‐B43 in other cancer types. Abstract : The current study provides bioinformatics and experimental data leading to the verification of a novel microRNA, which is located in the intronic region of the cadherin 4 gene. This novel microRNA was endogenously detected in breast cancer cell lines. Further Gene Ontology enrichment and pathway analysis of hsa‐miR‐B43 target genes, together with some experimental results suggested a possible function in promoting tumor metastasis.